Religiosity and Subjective Well-Being amongst Institutionalized Elderly in Pakistan - Fouzia Gull (Health Promotion Perspectives, 2013)
Background: In Pakistan, the issue of institutionalized elderly is a neg¬lected area and little is known about their subjective conditions. The present study was con-ducted in 2012 which examined the relationship between religiosity and subjective well being amongst institutionalized el¬derly people. Methods: Data was collected from 100 adults above the age of 60 years in Lahore, Pakistan, through purposive sampling strategy. Religiosity was measured through Religiosity Index, while Trait Well Being Inventory was used to assess subjective well being. Results: Pearson product moment correlation coefficient and regression analysis were used for the analysis of the data, which revealed that reli¬giosity has a significant positive relationship with life satisfaction. How¬ever, no association was found between religiosity and mood level. More¬over, regression analysis indicated that religiosity positively predicted life satisfaction among elderly. Conclusion: The current research would create awareness and urge the policy makers to look into this social issue and provide better long term care to the residents of old homes.